(untitled) (Ogigia. Revista Electrónica de Estudios Hispánicos, 2016)
This article analyses the importance of the presence of the social traveller 2.0 in the act of communication on tourist websites, specifically on the homepages of official tourism websites in Spain (spain.info) and France (france.fr). Through qualitative analysis, the study allows for similarities and differences between the websites to be identified and interpreted, as well as the repercussions for communication in tourism promotion.